1976
DOI: 10.1042/bst0040347
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV, a Kidney Microvillus Serine Proteinase: Evidence for its Large Subunit Molecular Weight and Endopeptidase Activity

Abstract: Dipeptidyl peptidase IV was first described by Hopsu-Havu & Glenner (1966) and purified from kidney by Hopsu-Havu et al. (1968). Enzymes of this class (for a review, see McDonald et al., 1971) hydroylse dipeptides from the N-terminus of susceptible substrates. Barth et al. (1974) demonstrated that dipeptidyl peptidase IV exhibits two specificities, involving substrates of the types X-Pro-Y and X-Ala-Y, and that it is sensitive to inhibition by di-isopropyl phosphorofluoridate. The enzyme is one of a group of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The heterogenous S9b family of DPPs (dipeptidyl peptidases) is a growing family of serine peptidases, which is characterized by the first identified member DPP-IV (also called CD26; EC 3.4.14.5) [1]. DPP-IV was first identified by Hopsu-Havu and Glenner [2] as an enzyme that possesses a glycylproline β-naphthylamidase activity, and it was later shown that DPP-IV has a general ability to cleave prolyl and alanyl peptide bonds at the penultimate position from the N-terminus [3][4][5][6]. Initially, the observed specificity of DPP-IV was assumed to be unique, but other DPPs and related peptidases with similar specificity have since been identified [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogenous S9b family of DPPs (dipeptidyl peptidases) is a growing family of serine peptidases, which is characterized by the first identified member DPP-IV (also called CD26; EC 3.4.14.5) [1]. DPP-IV was first identified by Hopsu-Havu and Glenner [2] as an enzyme that possesses a glycylproline β-naphthylamidase activity, and it was later shown that DPP-IV has a general ability to cleave prolyl and alanyl peptide bonds at the penultimate position from the N-terminus [3][4][5][6]. Initially, the observed specificity of DPP-IV was assumed to be unique, but other DPPs and related peptidases with similar specificity have since been identified [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DPPIV cleaves dipeptides from the N-terminus of oligopeptides with proline or alanine in their penultimate position [3,4]. Physiological substrates of DPPIV include chemokines, peptide hormones and neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…This protein was later identified as a serine protease that preferably cleaves prolyl and alanyl peptide bonds at the penultimate position from the N-terminus. [22][23][24] DPP4 is expressed as a glycoprotein on the surface of cells of most tissues, including kidney, liver, intestine, placenta, prostate, skin, lymphocytes, and endothelial cells. DPP4 is catalytically active as a dimer.…”
mentioning
confidence: 99%